Competitive Option Preferences of Daring and Hybrid Course Models In The Faculty Of Engineering: A Game Theory Approach - Sukwika, Tatan; Situmorang, Marningot T. Natalis (The Graduate School of Sahid University, 2024)
Since the COVID-19 pandemic, there has been a shift in the educational paradigm towards daring and hybrid learning models, especially at the Faculty of Engineering, Sahid University. Students are faced with the choice of daring or hybrid courses, which gives rise to differences in preferences and impacts on learning effectiveness. This research aims to identify the factors that most influence student preferences in choosing daring and hybrid study models. The research method uses a quantitative research design. An daring survey was distributed to Faculty of Engineering students with structured questions designed to identify preferences regarding lecture models. Samples were taken randomly from the student population of the Faculty of Engineering. Finally, the survey data was analyzed quantitatively using statistical methods such as logistic regression and factor analysis using a Game Theory approach. Based on the processing results using the POM-QM application, it is known that the Daring and Hybrid learning models show optimal values. The payoff value is 2.0, meaning that both learning models have their strategies for student preferences. Based on the maximin and minimax output, the respective values are -1 and 5.